متطلبات تطوير صناعة التأمين التكافلي في الجزائر على ضوء التجارب الدولية '' تجربة شركة سلامة للتأمينات '' - بالقط عائشة; بالقط بثينة; الشارف فاطمة (جامعة الوادي University of Eloued, 2025)
"تهدف هذه الدراسة إلى تحليل واقع التأمين التكافلي في الجزائر وتحديد متطلبات تطويره، في ظل التحديات التي تعيق نموه، مستنيرة بالتجربتين الرائدتين في السعودية وماليزيا. وتم اختيار شركة ""سلامة للتأمينات"" كنموذج تطبيقي يعكس خصوصيات السوق الجزائري. تتمحور إشكالية البحث حول التساؤل التالي: ما المتطلبات الأساسية لتطوير صناعة التأمين التكافلي في الجزائر في ضوء التجارب الدولية؟ وللإجابة عنه، تم اعتماد المنهج الوصفي التحليلي والمنهج المقارن. تناولت الدراسة الإطار النظري للتأمين التكافلي من حيث المفهوم والنشأة والمبادئ، وبيّنت الفروق الجوهرية بينه وبين التأمين التقليدي، كما عرضت أبرز ملامح التجربتين السعودية والماليزية كنماذج ناجحة في التنظيم والرقابة والتوسع السوقي، أما في الجانب التطبيقي، فقد تم تحليل تجربة شركة ""سلامة للتأمينات""، وأظهرت النتائج وجود عقبات تتعلق بضعف الإطار التشريعي، وغياب رقابة شرعية فعالة، وضعف التكوين والوعي التأميني لدى الجمهور، وقد خلصت الدراسة إلى أن النهوض بصناعة التأمين التكافلي في الجزائر يتطلب إصدار تشريعات ملائمة، وتأسيس هيئات رقابة شرعية، وتأهيل الكفاءات المتخصصة، وبناء شراكات مع المؤسسات المالية الإسلامية، مع استلهام النماذج التنظيمية للدول المتقدمة في هذا المجال. وتوصي الدراسة بوضع إستراتيجية وطنية متكاملة لتطوير القطاع، تعزز من الشمول المالي وتحقيق العدالة الاجتماعية وفقاً لمبادئ الشريعة الإسلامية. This study aims to analyze the reality of Takaful insurance in Algeri and identify the requirements for its development in light of the challenges hindering its growth. It draws upon the leading experiences in Saudi Arabia and Malaysia, using “Salama Insurance Company” as a model applied to reflect the specificities of the Algerian market. The research problem revolves around the following question: What are the basic requirements for developing the Takaful insurance industry in Algeria in light of international experiences? To answer this, the study adopts a descriptive-analytical and comparative approach. The theoretical framework of the study addresses Takaful insurance in terms of concepts, principles, and highlights the fundamental differences between it and traditional insurance. It also presents key features of the successful Saudi and Malaysian models in terms of regulation, oversight, and market expansion, In the practical part, the experience of “Salama Insurance Company” was analyzed. The results showed several obstacles related to a weak legislative framework, absence of effective Sharia oversight, weak public awareness and understanding of Takaful insurance. The study concluded that in order to advance the Takaful insurance industry in Algeria, there is a need to issue appropriate legislation, establish Sharia oversight bodies, train qualified experts, and build partnerships with Islamic financial institutions. In addition to drawing from the experiences of advanced countries in this field, the study recommends developing a comprehensive national strategy to develop the sector, enhance financial inclusion, and achieve social justice according to the principles of Islamic Sharia.
ماستر
Keywords: تأمين تكافلي، تأمين تقليدي، مؤسسة مالية إسلامية، نافذة تأمين تكافلي، سلامة للتأمينات; Islamic finance; Takaful insurance; traditional insurance; Islamic institution; Takaful insurance window; Salama Insurance